The Effect of Animation Teaching Materials on Soccer Game Tactics and Strategies Knowledge - Faizal, Faizal; Firdausi, Dzihan Khilmi Ayu; Andriadi, Andriadi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
This test is motivated by the problem of student learning outcomes, especially information about soccer strategies and tactics which are still relatively low. The motivation behind this review is to determine the impact of animation on knowledge of the strategy and tactics soccer games on 12th grade Pangkalpinang Senior High School 3. This test provides a reference for educators in expanding student information. This research is an experimental quantitative research. Determination of the sample by purposive sampling procedure. The sample used is 32 students. This experiment uses a Pre-Experimental Design with a trial plan of the One Group Pretest-Posttest Plan. The data testing method used One Sample t-test (Pretest-Posttest). After testing the presumption using the t-test, it is obtained that tcount = 3.893 and ttable with a degree of 5% = 1.696, then Ha is recognized and H0 is rejected. Thus, it can be concluded that there is an effect of animation teaching materials on the knowledge of strategy and tactics soccer game on 12th grade Pangkalpinang Senior High School 3.